Inflammatory bowel disease and lung - (:unkn) unknown (My University, 2006)
Ulcerative colitis and Crohn's disease are associated with a variety of systemic manifestations. Pulmonary disease has been described much less frequently than other organ systems, yet more than 400 cases have been reported. Lung and gastrointestinal system are originated from primitive gut and they have same pathogenetic changes in these patients. Major patterns of pulmonary disease associated with inflammatory bowel disease (IBD) are pleuritis, airway disease, interstitial lung disease, necrobiotic nodules, pulmonary eosinophilia, thromboembolic disease, vasculitis, granulomatous lung disease, etc. Colectomy may aggravate respiratory symptoms. Drug induced disease must be kept in mind in patients taking sulfasalazine, mesalamine, methotrexate, and anti-TNF-alpha. Latent pulmonary abnormalities are evident either at pulmonary function tests or induced sputum or bronchoalveolar lavage, have been also reported in patients with inflammatory bowel disease in the absence of clinical evidence of airway disease. The treatment of IBD related respiratory involvement depends on the specific pattern of involvement, if left untreated, especially in airway disease, puts the patient at risk of developing irreversible destruction of the air passage. A high degree of suspicion is necessary to detect early the respiratory disease in association with any form of bowel disease.
Keywords: Humans; Crohn Disease; Colitis, Ulcerative; Lung Diseases